Neuroimaging in the Epileptic Baboon - Szabo, C. Akos; Salinas, Felipe S. (Frontiers in Veterinary Science, 2022)
Characterization of baboon model of genetic generalized epilepsy (GGE) is driven both electroclinically and by successful adoption of neuroimaging platforms, such as magnetic resonance imaging (MRI) and positron emission tomography (PET). Based upon its phylogenetic proximity and similar brain anatomy to humans, the epileptic baboon provides an excellent translational model. Its relatively large brain size compared to smaller nonhuman primates or rodents, a gyrencephalic structure compared to lissencephalic organization of rodent brains, and the availability of a large pedigreed colony allows exploration of neuroimaging markers of diseases. Similar to human idiopathic generalized epilepsy (IGE), structural imaging in the baboon is usually normal in individual subjects, but gray matter volume/concentration (GMV/GMC) changes are reported by statistical parametric mapping (SPM) analyses. Functional neuroimaging has been effective for mapping the photoepileptic responses, the epileptic network, altered functional connectivity of physiological networks, and the effects of anti-seizure therapies. This review will provide insights into our current understanding the baboon model of GGE through functional and structural imaging.